Microporous membrane for power storage device
By using the polyolefin microporous membrane crosslinking structure caused by functional groups in lithium-ion batteries, it optimizes its film rupture resistance and safety at high temperatures, and solves the increase in internal stress and battery deformation caused by crosslinking structures in the prior art in solving the problem of the increase in internal stress and battery deformation caused by crosslinking structures in the prior art. Problem, achieving more stable battery performance.
Patent Information
- Application Number
- CN202210691584.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-18
- Filing Date
- 2020-02-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-02-18
AI Technical Summary
In the prior art, when manufacturing microporous membranes for lithium-ion batteries, the crosslinking structure is prone to increase internal stress and battery deformation at high temperatures, and the crosslinking method is uneven, affecting the safety and performance of the battery.
By introducing functional groups into the polyolefin microporous membrane, it forms a crosslinked structure in the battery environment, satisfying specific melt flow rate, molecular weight ratio and density conditions, and optimizing the mechanical orientation rate through wide-angle X-ray scattering measurement to form a non- The crystal section cross-linking structure is used to improve film rupture resistance and safety.
It is achieved to maintain the strength and pore properties of the microporous membrane at high temperatures, improve the cycle stability and safety of the battery, and avoid the increase in internal stress and battery deformation caused by the crosslinked structure.
Smart Images

Figure CN115000625B_ABST
Abstract
Description
[0001] The present application is a divisional application of an application filed on February 18, 2020, with application number 202010099276.5 and invention name “Microporous membrane for power storage device”. Technical Field
[0002] The present invention relates to a microporous film for a power storage device, etc. Background Art
[0003] Microporous membranes are widely used as separation membranes and separators for separation or selective permeation of various substances, and examples of their use include fine filtration membranes, fuel cell diaphragms, capacitor diaphragms, or functional membrane matrix materials for filling pores with functional materials to exhibit new functions, and diaphragms for power storage devices. Among them, polyolefin microporous membranes can be suitably used as lithium ion battery diaphragms widely used in notebook personal computers, mobile phones, digital cameras, etc.
[0004] In order to ensure the safety of the battery, it is proposed to achieve both the startup shutdown function and the increase of the membrane rupture temperature by forming a cross-linked structure in the diaphragm (Patent Documents 1 to 8). For example, Patent Documents 1 to 6 record the silane cross-linked structure formed by the contact of a diaphragm containing a silane-modified polyolefin with water. Patent Document 7 records the cross-linked structure formed by ring-opening norbornene by irradiation with ultraviolet rays, electron beams, etc. Patent Document 8 records that the insulating layer of the diaphragm contains a (meth) acrylic copolymer with a cross-linked structure, a styrene-butadiene rubber binder, etc.
[0005] For lithium-ion battery components, positive electrodes, negative electrode materials, electrolytes and separators are used. Among these components, for separators, from the perspective of their suitability as insulating materials, it is required to be inert for electrochemical reactions or surrounding components. On the other hand, the negative electrode material of lithium-ion batteries has established a technology for suppressing the decomposition of electrolytes on the negative electrode surface by forming a solid electrolyte interface (SEI) by utilizing chemical reactions during initial charging since its initial development (non-patent literature 1). In addition, even if polyolefin resins are used in separators, oxidation reactions are induced on the positive electrode surface at high voltages, and cases of blackening of separators, surface degradation, etc. have also been reported.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 9-216964
[0009] Patent Document 2: International Publication No. 97 / 44839
[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 11-144700
[0011] Patent Document 4: Japanese Patent Application Laid-Open No. 11-172036
[0012] Patent Document 5: Japanese Patent Application Publication No. 2001-176484
[0013] Patent Document 6: Japanese Patent Application Publication No. 2000-319441
[0014] Patent Document 7: Japanese Patent Application Publication No. 2011-071128
[0015] Patent Document 8: Japanese Patent Application Publication No. 2014-056843
[0016] Non-patent literature
[0017] Non-patent document 1: Lithium-ion secondary battery (2nd edition) Published by Nikkan Kogyo Shimbun Summary of the invention
[0018] Problem that the invention aims to solve
[0019] In recent years, mobile device-mounted or vehicle-mounted lithium-ion secondary batteries have gradually become high-power and high-energy-density. On the other hand, the battery cell is required to be miniaturized and have stable cycle discharge and charge performance during long-term use. Therefore, for the manufacture of microporous membranes that can be used as battery separators, strength and open porosity are considered essential. Furthermore, the level of battery safety is also more stringent than before. As also described in Patent Documents 1 and 2, a diaphragm with a shutdown function and high-temperature membrane rupture and a stable manufacturing method thereof are expected. In this regard, as a shutdown temperature level, the lower the temperature, the more preferred it is. In addition, as a membrane rupture temperature level, the higher the temperature, the more preferred it is.
[0020] However, the cross-linking methods described in patent documents 1 to 8 are all carried out in the manufacturing process of the microporous film or in batches just after the microporous film is made. Therefore, after the cross-linked structure described in patent documents 1 to 8 is formed, the microporous film must be coated and cut in order to be used as a separator, and the internal stress will increase in the subsequent stacking / winding process with the electrode, so the produced power storage device sometimes deforms. For example, if a cross-linked structure is formed by heating, the internal stress of the separator having the cross-linked structure sometimes increases at normal temperature or room temperature. In addition, if a cross-linked structure is formed by irradiating the microporous film with light such as ultraviolet rays and electron beams, sometimes the irradiation of light becomes uneven and the cross-linked structure becomes uneven. It can be considered that this is because: the crystal part of the resin constituting the microporous film is easily cross-linked due to the electron beam.
[0021] In view of the above problems, the present invention aims to improve the rupture resistance of a microporous membrane at high temperature without impairing the strength and porosity of the microporous membrane, and to achieve both device characteristics of a power storage device using the microporous membrane as a separator and high safety in a nail penetration test.
[0022] Solutions for solving problems
[0023] The above-mentioned problems are solved by the following technical means. [1]
[0025] A microporous membrane for a power storage device, comprising polyolefin, wherein:
[0026] The polyolefin has one or more functional groups, and
[0027] After being housed in the power storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the power storage device, or (3) the functional groups react with other types of functional groups to form a cross-linked structure.
[0028] The aforementioned polyolefin satisfies the following conditions (A) to (C):
[0029] (A) a melt flow rate (MFR) of 3.0 g / 10 min or less when measured under conditions of a temperature of 230° C. and a mass of 2.16 kg;
[0030] (B) the value obtained by dividing the weight average molecular weight Mw by the number average molecular weight Mn (Mw / Mn) is 15 or less; and
[0031] (C) Density: 0.85 g / cm 3 above,
[0032] Furthermore, the microporous membrane for the power storage device satisfies the following condition (D):
[0033] (D) The ratio of the orientation ratio in the machine direction (MD) to the transverse direction (TD), MD / TD, measured by wide-angle X-ray scattering is 1.3 or more. [2]
[0035] The microporous membrane for a power storage device according to item 1, wherein the cross-linked structure is formed by (1) a condensation reaction of the functional groups. [3]
[0037] The microporous membrane for an electricity storage device according to item 1, wherein the cross-linked structure is formed by (2) a reaction between the functional group and a chemical substance inside the electricity storage device. [4]
[0039] The microporous membrane for an electricity storage device according to item 1 or 3, wherein the chemical substance is any of an electrolyte, an electrolyte solution, an electrode active material, an additive, or a decomposition product thereof contained in the electricity storage device. [5]
[0041] The microporous membrane for a power storage device according to item 1, wherein the cross-linked structure is formed by (3) a reaction between the functional group and another type of functional group. [6]
[0043] The microporous membrane for an electrical storage device according to any one of items 1 to 5, wherein the microporous membrane for an electrical storage device has a mixed storage modulus ratio (R E’x ) is 1.2 to 20 times.
[0044] R E’X =E' Z / E' Z0 (I)
[0045] {where E' Z The storage modulus is measured in the temperature range of 160° C. to 300° C. after the crosslinking reaction of the microporous membrane for the power storage device is carried out in the power storage device, and
[0046] E' Z0 The storage modulus is measured at a temperature range of 160° C. to 300° C. before the microporous membrane for an electricity storage device is assembled into the electricity storage device, and E′ Z or E' Z0 The measurement conditions of the storage modulus are defined by the following constitutions (i) to (iv).
[0047] (i) Dynamic viscoelasticity measurements were performed under the following conditions:
[0048] Atmosphere: Nitrogen
[0049] · Measurement device used: RSA-G2 (manufactured by TA Instruments)
[0050] Sample film thickness: 5 μm to 50 μm (all samples are measured on one sheet regardless of their film thickness)
[0051] ·Measurement temperature range: -50~300℃
[0052] Heating rate: 10℃ / min
[0053] ·Measurement frequency: 1Hz
[0054] Deformation mode: Sine wave stretching mode (Linear tension)
[0055] Initial value of static tensile load: 0.5N
[0056] Initial (at 25°C) gap distance: 25mm
[0057] Automatic strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N).
[0058] (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each cycle motion, and the sinusoidal load refers to the oscillating stress centered on the static tensile load.
[0059] (iii) Sine wave tensile mode refers to measuring vibration stress while performing periodic motion at a fixed amplitude of 0.2%. At this time, the gap distance and static tensile load are changed in such a way that the difference between the static tensile load and the sine wave load is within 20%, and the vibration stress is measured. When the sine wave load is less than 0.02N, the amplitude value is amplified in such a way that the sine wave load is within 5N and the increase in the amplitude value is within 25%, and the vibration stress is measured.
[0060] (iv) The storage modulus is calculated from the relationship between the obtained sinusoidal wave load and the amplitude value and the following formula:
[0061] ζ * =ζ 0 Exp[i(ωt+δ)],
[0062] ε * =ε 0 Exp(iωt),
[0063] ζ * =E * ·ε *
[0064] E * =E'+iE"
[0065] (where ζ * :Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : complex modulus, E': storage modulus, E': loss modulus
[0066] Vibration stress: Sinusoidal load / initial cross-sectional area
[0067] Static tensile load: The load at the minimum point of vibration stress in each cycle (the minimum point of gap distance in each cycle)
[0068] Sine wave load: The difference between the measured vibration stress and the static tensile load)} [7]
[0070] A microporous membrane for a power storage device, comprising polyolefin, wherein:
[0071] The microporous membrane for a power storage device has an amorphous portion crosslinked structure formed by crosslinking an amorphous portion of the polyolefin.
[0072] The aforementioned polyolefin satisfies the following conditions (A) to (C):
[0073] (A) a melt flow rate (MFR) of 3.0 g / 10 min or less when measured under conditions of a temperature of 230° C. and a mass of 2.16 kg;
[0074] (B) the value obtained by dividing the weight average molecular weight Mw by the number average molecular weight Mn (Mw / Mn) is 15 or less; and
[0075] (C) Density: 0.85 g / cm 3 above,
[0076] Furthermore, the microporous membrane for the power storage device satisfies the following condition (D):
[0077] (D) The ratio of the orientation ratio in the machine direction (MD) to the transverse direction (TD), MD / TD, measured by wide-angle X-ray scattering is 1.3 or more. [8]
[0079] The microporous membrane for a power storage device according to item 7, wherein the amorphous portion is selectively cross-linked. [9]
[0081] The microporous membrane for an electrical storage device according to item 7 or 8, wherein the hybrid storage modulus ratio (R E’mix ) is 1.2 to 20 times.
[0082] R E’mix =E' / E' 0 (II)
[0083] {wherein, E' is the storage modulus measured at 160°C to 300°C when the microporous membrane for a power storage device has the amorphous portion crosslinked structure, and,
[0084] E' 0 The storage modulus of the microporous film for a power storage device having no amorphous crosslinked structure measured at 160°C to 300°C, and E' or E' 0The measurement conditions of the storage modulus are defined by the following constitutions (i) to (iv).
[0085] (i) Dynamic viscoelasticity measurements were performed under the following conditions:
[0086] Atmosphere: Nitrogen
[0087] · Measurement device used: RSA-G2 (manufactured by TA Instruments)
[0088] Sample film thickness: 5 μm to 50 μm (all samples are measured on one sheet regardless of their film thickness)
[0089] ·Measurement temperature range: -50~300℃
[0090] Heating rate: 10℃ / min
[0091] ·Measurement frequency: 1Hz
[0092] Deformation mode: Sine wave stretching mode (Linear tension)
[0093] Initial value of static tensile load: 0.5N
[0094] Initial (at 25°C) gap distance: 25mm
[0095] Automatic strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N).
[0096] (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each cycle motion, and the sinusoidal load refers to the oscillating stress centered on the static tensile load.
[0097] (iii) Sine wave tensile mode refers to measuring vibration stress while performing periodic motion at a fixed amplitude of 0.2%. At this time, the gap distance and static tensile load are changed in such a way that the difference between the static tensile load and the sine wave load is within 20%, and the vibration stress is measured. When the sine wave load is less than 0.02N, the amplitude value is amplified in such a way that the sine wave load is within 5N and the increase in the amplitude value is within 25%, and the vibration stress is measured.
[0098] (iv) The storage modulus is calculated from the relationship between the obtained sinusoidal wave load and the amplitude value and the following formula:
[0099] ζ * =ζ 0 Exp[i(ωt+δ)],
[0100] ε * =ε 0 Exp(iωt),
[0101] ζ * =E * ·ε *
[0102] E * =E'+iE"
[0103] (where ζ * :Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : complex modulus, E': storage modulus, E': loss modulus
[0104] Vibration stress: Sinusoidal load / initial cross-sectional area
[0105] Static tensile load: The load at the minimum point of vibration stress in each cycle (the minimum point of gap distance in each cycle)
[0106] Sine wave load: The difference between the measured vibration stress and the static tensile load).}
[10]
[0108] The microporous membrane for a power storage device according to any one of items 1 to 9, wherein the polyolefin has an MFR of 0.25 g / 10 min or more, an Mw / Mn of 4.0 or more, and a density of 1.1 g / cm 3 The following, and
[0109] The orientation ratio MD / TD of the microporous film for an electricity storage device is 3.0 or less.
[11]
[0111] The microporous membrane for an electrical storage device according to any one of items 1 to 10, wherein the polyolefin is polypropylene.
[12]
[0113] A microporous membrane for an electricity storage device, comprising polypropylene, wherein:
[0114] The polypropylene has one or more functional groups and is β-crystal active.
[0115] After being housed in a power storage device, the microporous membrane for a power storage device forms a crosslinked structure by (1) condensation reaction between the functional groups, (2) reaction between the functional groups and chemical substances inside the power storage device, or (3) reaction between the functional groups and other types of functional groups.
[13]
[0117] The microporous membrane for a power storage device according to item 12, wherein the cross-linked structure is formed by (1) a condensation reaction of the functional groups.
[14]
[0119] The microporous membrane for an electricity storage device according to item 12, wherein the cross-linked structure is formed by (2) a reaction between the functional group and a chemical substance inside the electricity storage device.
[15]
[0121] The microporous membrane for an electricity storage device according to item 12 or 14, wherein the chemical substance is any of an electrolyte, an electrolyte solution, an electrode active material, an additive, or a decomposition product thereof contained in the electricity storage device.
[16]
[0123] The microporous membrane for a power storage device according to item 12, wherein the cross-linked structure is formed by (3) a reaction between the functional group and another type of functional group.
[17]
[0125] The microporous membrane for an electrical storage device according to any one of items 12 to 16, wherein the hybrid storage modulus ratio (R E’x ) is 1.2 to 20 times.
[0126] R E’X =E' Z / E' Z0 (I)
[0127] {where E' Z The storage modulus is measured in a temperature range of 160° C. to 300° C. after the crosslinking reaction of the microporous membrane for an electricity storage device is carried out in an electricity storage device, and
[0128] E' Z0 is the storage modulus measured in the temperature range of 160° C. to 300° C. before the porous membrane for an electricity storage device is assembled into the electricity storage device, and E′ Z or E' Z0 The measurement conditions of the storage modulus are defined by the following constitutions (i) to (iv).
[0129] (i) Dynamic viscoelasticity measurements were performed under the following conditions:
[0130] Atmosphere: Nitrogen
[0131] · Measurement device used: RSA-G2 (manufactured by TA Instruments)
[0132] Sample film thickness: 5 μm to 50 μm (all samples are measured on one sheet regardless of their film thickness)
[0133] ·Measurement temperature range: -50~300℃
[0134] Heating rate: 10℃ / min
[0135] ·Measurement frequency: 1Hz
[0136] Deformation mode: Sine wave stretching mode (Linear tension)
[0137] Initial value of static tensile load: 0.5N
[0138] Initial (at 25°C) gap distance: 25mm
[0139] Automatic strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N).
[0140] (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each cycle motion, and the sinusoidal load refers to the oscillating stress centered on the static tensile load.
[0141] (iii) Sine wave tensile mode refers to measuring vibration stress while performing periodic motion at a fixed amplitude of 0.2%. At this time, the gap distance and static tensile load are changed in such a way that the difference between the static tensile load and the sine wave load is within 20%, and the vibration stress is measured. When the sine wave load is less than 0.02N, the amplitude value is amplified in such a way that the sine wave load is within 5N and the increase in the amplitude value is within 25%, and the vibration stress is measured.
[0142] (iv) The storage modulus is calculated from the relationship between the obtained sinusoidal wave load and the amplitude value and the following formula:
[0143] ζ * =ζ 0 Exp[i(ωt+δ)],
[0144] ε * =ε 0 Exp(iωt),
[0145] ζ * =E * ·ε *
[0146] E * =E'+iE"
[0147] (where ζ * :Vibration stress, ε *: strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : complex modulus, E': storage modulus, E': loss modulus
[0148] Vibration stress: Sinusoidal load / initial cross-sectional area
[0149] Static tensile load: The load at the minimum point of vibration stress in each cycle (the minimum point of gap distance in each cycle)
[0150] Sine wave load: The difference between the measured vibration stress and the static tensile load).}
[18]
[0152] A microporous membrane for an electricity storage device comprises polypropylene, wherein the polypropylene is β-crystal active and has an amorphous portion crosslinked structure formed by crosslinking an amorphous portion of the polypropylene.
[19]
[0154] The microporous membrane for a power storage device according to Item 18, wherein the amorphous portion is selectively cross-linked.
[20]
[0156] The microporous membrane for an electrical storage device according to item 18 or 19, wherein the hybrid storage modulus ratio (R E’mix ) is 1.2 to 20 times.
[0157] R E’mix =E' / E' 0 (II)
[0158] {wherein, E' is the storage modulus measured at 160°C to 300°C when the microporous membrane for a power storage device has the amorphous portion crosslinked structure, and,
[0159] E' 0 The storage modulus of the microporous film for a power storage device having no amorphous crosslinked structure measured at 160°C to 300°C, and E' or E' 0 The measurement conditions of the storage modulus are defined by the following constitutions (i) to (iv).
[0160] (i) Dynamic viscoelasticity measurements were performed under the following conditions:
[0161] Atmosphere: Nitrogen
[0162] · Measurement device used: RSA-G2 (manufactured by TA Instruments)
[0163] Sample film thickness: 5 μm to 50 μm (all samples are measured on one sheet regardless of their film thickness)
[0164] ·Measurement temperature range: -50~300℃
[0165] Heating rate: 10℃ / min
[0166] ·Measurement frequency: 1Hz
[0167] Deformation mode: Sine wave stretching mode (Linear tension)
[0168] Initial value of static tensile load: 0.5N
[0169] Initial (at 25°C) gap distance: 25mm
[0170] Automatic strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N).
[0171] (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each cycle motion, and the sinusoidal load refers to the oscillating stress centered on the static tensile load.
[0172] (iii) Sine wave tensile mode refers to measuring vibration stress while performing periodic motion at a fixed amplitude of 0.2%. At this time, the gap distance and static tensile load are changed in such a way that the difference between the static tensile load and the sine wave load is within 20%, and the vibration stress is measured. When the sine wave load is less than 0.02N, the amplitude value is amplified in such a way that the sine wave load is within 5N and the increase in the amplitude value is within 25%, and the vibration stress is measured.
[0173] (iv) The storage modulus is calculated from the relationship between the obtained sinusoidal wave load and the amplitude value and the following formula:
[0174] ζ * =ζ 0 Exp[i(ωt+δ)],
[0175] ε * =ε 0 Exp(iωt),
[0176] ζ * =E * ·ε *
[0177] E * =E'+iE"
[0178] (where ζ * :Vibration stress, ε *: strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : complex modulus, E': storage modulus, E': loss modulus
[0179] Vibration stress: Sinusoidal load / initial cross-sectional area
[0180] Static tensile load: The load at the minimum point of vibration stress in each cycle (the minimum point of gap distance in each cycle)
[0181] Sine wave load: The difference between the measured vibration stress and the static tensile load).} [twenty one]
[0183] The microporous membrane for an electrical storage device according to any one of items 12 to 20, wherein the microporous membrane for an electrical storage device comprises a homopolypropylene (A) satisfying the following conditions (P1) to (P3), and a polypropylene (B) having a functional group which does not satisfy at least one of the conditions (P1) to (P3) as the polypropylene:
[0184] (P1) MFR when measured under the conditions of a temperature of 230°C and a mass of 2.16 kg is 2.5 g / 10 min or less;
[0185] (P2) the value obtained by dividing the weight average molecular weight Mw by the number average molecular weight Mn (Mw / Mn) is 10 or less; and
[0186] (P3) density is 0.89g / cm 3 above. [twenty two]
[0188] The microporous membrane for a power storage device according to Item 21, wherein the content of the polypropylene (B) is 4% by mass or more and 30% by mass or less. [twenty three]
[0190] The microporous membrane for a power storage device according to item 21 or 22, wherein the polypropylene (B) is a silane-modified polypropylene. [twenty four]
[0192] The microporous membrane for a power storage device according to any one of items 21 to 23, wherein the homopolypropylene (A) has an MFR of 0.25 g / 10 min or more, an Mw / Mn of 4.9 or more, and a density of 0.96 g / cm 3 the following.
[0193] Effects of the Invention
[0194] According to the present invention, the strength and porosity of the microporous membrane for the power storage device are not impaired, the resistance to film breakage at high temperature can be improved, and the battery characteristics of the power storage device having the microporous membrane as a separator and the high safety in the nail penetration test can be taken into account. In addition, according to the present invention, a cross-linked structure may not be formed during or immediately after the film-making process, thereby suppressing the increase in the internal stress of the separator and the deformation after the power storage device is manufactured, and / or, even without using higher energy such as light irradiation or heating, a cross-linked structure can be given to the separator. BRIEF DESCRIPTION OF THE DRAWINGS
[0195] Figure 1 This is a schematic diagram for explaining a crystalline polymer having a high-order structure divided into crystalline lamellae (crystalline parts), an amorphous part, and an intermediate layer part therebetween.
[0196] Figure 2 This is a schematic diagram for explaining the crystal growth of polyolefin molecules.
[0197] Figure 3 This is an example of a graph for explaining the relationship between temperature and storage modulus, comparing the storage modulus of a reference film and a cross-linked film in the temperature range of -50°C to 310°C, and showing the transition temperature between the rubbery flat region and the crystalline melt flow region.
[0198] Figure 4 This is an example of a graph for explaining the relationship between temperature and loss modulus, comparing the loss modulus of a reference film and a cross-linked film in the temperature range of -50°C to 310°C, and showing the transition temperature between the rubbery flat region and the crystalline melt flow region. DETAILED DESCRIPTION
[0199] Hereinafter, the present specific embodiment (hereinafter abbreviated as "embodiment") will be described in detail. It should be noted that the present invention is not limited to the following embodiment, and various modifications can be made within the scope of the gist thereof.
[0200] [Microporous membrane for power storage device]
[0201] The microporous membrane may be a composite resin membrane formed of a single or multiple polyolefin resins, or a polyolefin resin and other resins, and may have a plurality of micropores. The microporous membrane containing a polyolefin resin as a main component (hereinafter also referred to as a polyolefin microporous membrane) contains 50% by mass or more of the polyolefin resin relative to the membrane mass.
[0202] From the viewpoint of resistance to redox degradation and dense and uniform porous structure, the polyolefin-based microporous membrane is preferably used to form a power storage device, more preferably as a constituent material of a power storage device, further preferably as a separator for a power storage device, and particularly preferably as a separator for a lithium ion battery. In this specification, a separator for a power storage device (hereinafter sometimes abbreviated as "separator") refers to a component that is arranged between multiple electrodes in a power storage device and has ion permeability and shutdown characteristics as required. The separator includes a microporous membrane and may further have any functional layer as desired.
[0203] [First embodiment and second embodiment]
[0204] The microporous membrane described in the first embodiment includes a polyolefin having one or more functional groups. After being housed in a power storage device, (1) the functional groups of the polyolefins undergo a condensation reaction with each other, (2) the functional groups of the polyolefins react with chemical substances inside the power storage device, or (3) the functional groups of the polyolefins react with other types of functional groups to form a cross-linked structure. In the first embodiment, the microporous membrane can form a cross-linked structure by any of the reactions (1) to (3) above, thereby maintaining strength and improving film breakage resistance at high temperatures above 150°C. For example, when the microporous membrane is housed in a power storage device as a separator, there is a tendency to take into account both device characteristics and safety.
[0205] Furthermore, in the first embodiment, the polyolefin contained in the microporous membrane satisfies the following conditions (A) to (C):
[0206] (A) a melt flow rate (MFR) of 3.0 g / 10 min or less when measured under conditions of a temperature of 230° C. and a mass of 2.16 kg;
[0207] (B) the value obtained by dividing the weight average molecular weight Mw by the number average molecular weight Mn (Mw / Mn) is 15 or less; and
[0208] (C) Density: 0.85 g / cm 3 above;
[0209] Furthermore, the microporous membrane satisfies the following condition (D):
[0210] (D) The ratio of the orientation ratio in the machine direction (MD) to the width direction (TD) measured by wide-angle X-ray scattering, MD / TD, is 1.3 or more. In the first embodiment, if the polyolefin and the microporous membrane satisfy conditions (A) to (D), the strength, film forming properties, productivity, and porosity of the microporous membrane tend to be improved.
[0211] Regarding condition (A), if the MFR of the polyolefin (PO) measured under the conditions of a temperature of 230°C and a mass of 2.16kg is 3.0g / 10 minutes or less, the strength of the obtained microporous membrane is likely to reach a qualified level. From the same point of view, the MFR of PO is preferably 0.25 to 2.9g / 10 minutes, more preferably 0.3 to 2.7g / 10 minutes, and further preferably 0.4 to 2.5g / 10 minutes. The MFR of the polyolefin (PO) measured under the conditions of a temperature of 230°C and a mass of 2.16kg can be 0.5g / 10 minutes or more, 0.6g / 10 minutes or more, 0.7g / 10 minutes or more, 0.8g / 10 minutes or more, 0.9g / 10 minutes or more, or 1.0g / 10 minutes or more. The MFR of the polyolefin (PO) measured at a temperature of 230° C. and a mass of 2.16 kg may be 2.3 g / 10 min or less, 2.0 g / 10 min or less, 1.8 g / 10 min or less, or 1.5 g / 10 min or less.
[0212] Regarding condition (B), if the dispersion degree (Mw / Mn) of PO is 15 or less, there is a tendency that both the film-forming property and the strength of the obtained PO can be taken into account. From the viewpoint of taking into account the film-forming property and the strength, the dispersion degree (Mw / Mn) of PO is preferably 4.0 to 13, more preferably 4.9 to 11, and further preferably 5.2 to 9.0. The dispersion degree (Mw / Mn) of PO can be 5.5 or more, 5.8 or more, 6.0 or more, 6.2 or more, or 6.5 or more. The dispersion degree (Mw / Mn) of PO can be 8.0 or less, 7.0 or less, or 6.5 or less.
[0213] Regarding condition (C), since PO density is closely related to PO crystallinity, when PO density is 0.85 g / cm 3 In the above case, the productivity of the microporous membrane is improved, which is particularly effective for the dry pore forming method. From the viewpoint of productivity and porosity, the PO density is preferably 0.85 g / cm 3 Above, preferably 0.88 g / cm 3 Above, or preferably 0.90 g / cm 3 In addition, the PO density is preferably 1.1 g / cm 3 Below, preferably 1.0 g / cm 3 Below, preferably 0.98 g / cm 3 Below, preferably 0.97 g / cm 3 Below, preferably 0.96 g / cm 3 Below, preferably 0.95 g / cm 3Below, preferably 0.94 g / cm 3 Below, preferably 0.93 g / cm 3 Below, or preferably less than 0.92 g / cm 3 Examples of PO include polypropylene and polyethylene.
[0214] Regarding condition (D), when the wide-angle X-ray scattering measurement of the microporous film is performed, if the orientation ratio MD / TD is 1.3 or more, there is a tendency that the microporosity, cross-linked structure and ion permeability of the film are suitable for the desired device characteristics. From the perspective of the suitability of the film properties and the device characteristics, the lower limit of the orientation ratio MD / TD is preferably 1.4 or more or 1.5 or more, and more preferably 1.6 or more. The upper limit of the orientation ratio MD / TD can be 4.0 or less, 3.5 or less, or 3.1 or less, depending on, for example, the film making process.
[0215] The microporous membrane described in the second embodiment includes β-crystal active polypropylene having one or more functional groups. After being accommodated in the power storage device, (1) the functional groups of the polypropylene undergo condensation reaction with each other, (2) the functional groups of the polypropylene react with the chemical substances inside the power storage device, or (3) the functional groups of the polypropylene react with other types of functional groups to form a cross-linked structure. In the second embodiment, if an unstretched sheet having β-crystals is prepared by melt extrusion of polypropylene having β-crystal activity, the prepared unstretched sheet is stretched to transform its crystal form into α-crystals with higher crystal density, and the difference in crystal density between the two is used to form micropores to obtain a microporous membrane, the obtained microporous membrane can form a cross-linked structure through any reaction in the above (1) to (3), thereby maintaining strength and improving the film breakage resistance at high temperatures above 150°C, and there is a tendency to take into account both the device characteristics and safety of the power storage device. The microporous membrane according to the second embodiment may include a single type or multiple types of polypropylenes. When including multiple types of polypropylenes, at least one of them has one or more types of functional groups and β-crystal activity.
[0216] In the first and second embodiments, it can be considered that the functional groups contained in polyolefins such as polypropylene will not be introduced into the crystalline part of the polyolefin, but will be cross-linked in the amorphous part. Therefore, after the microporous membranes described in the first and second embodiments are housed in the power storage device, they can form a cross-linked structure by utilizing the surrounding environment or the chemical substances inside the power storage device, thereby suppressing the increase of internal stress or deformation of the manufactured power storage device, which contributes to safety.
[0217] On the other hand, when the microporous membrane undergoes a cross-linking reaction before being housed in the power storage device and undergoes a winding / cutting process, the influence of stress such as tension generated during the process will remain. In this case, it is considered that when the stress is released after assembling the power storage device, it will cause damage due to deformation or stress concentration of the electrode winding, etc., which is not preferred.
[0218] In addition, in the first and second embodiments, a cross-linked structure may not be formed during the film forming process or immediately after the film forming process is completed. Therefore, when the microporous membrane is used as a diaphragm, the increase in internal stress and deformation after the storage device is manufactured can be suppressed, and / or, light irradiation or heating for forming a cross-linked structure is not used, which can help save energy.
[0219] [Third embodiment and fourth embodiment]
[0220] The microporous membrane described in the third embodiment includes polyolefin and has an amorphous crosslinked structure formed by crosslinking the amorphous part of the polyolefin. In the third embodiment, the amorphous crosslinked structure of the polyolefin can improve the film rupture resistance at high temperatures above 150°C, and when the microporous membrane is assembled into a power storage device as a separator, there is a tendency to take into account both device characteristics and safety.
[0221] Furthermore, in the third embodiment, the polyolefin contained in the microporous membrane satisfies the following conditions (A) to (C):
[0222] (A) a melt flow rate (MFR) of 3.0 g / 10 min or less when measured under conditions of a temperature of 230° C. and a mass of 2.16 kg;
[0223] (B) the value obtained by dividing the weight average molecular weight Mw by the number average molecular weight Mn (Mw / Mn) is 15 or less; and
[0224] (C) Density: 0.85 g / cm 3 above,
[0225] And the microporous membrane satisfies the following condition (D):
[0226] (D) The ratio of the orientation ratio in the machine direction (MD) to the transverse direction (TD), MD / TD, measured by wide-angle X-ray scattering is 1.3 or more.
[0227] In the third embodiment, if the polyolefin and the microporous membrane satisfy conditions (A) to (D), there is a tendency for the strength, film forming properties, productivity, porosity and ion permeability of the microporous membrane, and the characteristics of the storage device to be improved for the same reasons as conditions (A) to (D) described in the first embodiment.
[0228] The microporous membrane described in the fourth embodiment contains polypropylene with β-crystal activity and has an amorphous cross-linked structure formed by cross-linking the amorphous part of polypropylene. In the fourth embodiment, if an unstretched sheet with β-crystal is produced by melt extrusion of polypropylene with β-crystal activity, the produced unstretched sheet is stretched to transform its crystal form into α-crystal with higher crystal density, and the difference in crystal density between the two is used to form micropores to obtain a microporous membrane, then the obtained microporous membrane has an amorphous cross-linked structure, and therefore, the film breakage resistance at high temperatures above 150°C can be improved, and there is a tendency to take into account both the device characteristics and safety of the storage device. The microporous membrane described in the fourth embodiment may contain a single or multiple polypropylenes. When containing multiple polypropylenes, at least one of them has β-crystal activity.
[0229] In the third and fourth embodiments, it can be considered that the functional groups contained in polyolefins such as polypropylene will not be introduced into the crystalline part of the polyolefin, but cross-linking will occur in the amorphous part. Therefore, the microporous membrane described in the third and fourth embodiments can take into account both the shutdown function and the high-temperature rupture resistance of the film and suppress the increase of internal stress or the deformation of the produced power storage device, compared with the previous cross-linked microporous membrane that is easily cross-linked in the crystalline part and its surroundings, and thus can ensure the safety of the power storage device. From the same point of view, the amorphous part of the polyolefin contained in the microporous membrane described in the third and fourth embodiments is preferably selectively cross-linked, and more preferably more significantly cross-linked than the crystalline part.
[0230] 〔Cross-linking reaction mechanism〕
[0231] In the first embodiment, the second embodiment, the third embodiment, and the fourth embodiment, the cross-linking reaction mechanism and the cross-linking structure are not yet clear, but the present inventors consider the following (i) to (iv).
[0232] (I) Crystalline structure in polyolefin-based microporous membranes
[0233] like Figure 1 As shown in the figure, polyolefin resins represented by polyethylene are generally crystalline polymers, and have a high-order structure divided into crystalline lamellae (crystalline part), amorphous part, and an intermediate layer part between them. In the crystalline part and the intermediate layer part between the crystalline part and the amorphous part, the mobility of the polymer chain is low and cannot be cut, but in the solid viscoelasticity measurement, relaxation can be observed in the 0℃ to 120℃ region. On the other hand, the mobility of the polymer chain in the amorphous part is very high, and in the solid viscoelasticity measurement, it is observed in the -150℃ to -100℃ region. This is related to the relaxation of free radicals or the migration reaction of free radicals, cross-linking reactions, etc. described later.
[0234] In addition, the polyolefin molecules that make up the crystal are not single, but Figure 2 As shown in the example, after a plurality of polymer chains form small lamellae, the lamellae aggregate to form crystals. This phenomenon is difficult to observe directly. In recent years, it has been studied academically through simulation and has been clarified. It should be noted that in this specification, crystallization refers to the smallest crystal unit measured by X-ray structure analysis, which is a unit that can be calculated as a crystallite size. It can be predicted that even in the crystalline part (inside the lamellae), there is a part in the crystal that is not bound and has a slightly higher mobility.
[0235] (II) Cross-linking reaction mechanism based on electron beam
[0236] Next, the reaction mechanism of electron beam cross-linking (hereinafter referred to as EB cross-linking) of a polymer is as follows.
[0237] (i) Irradiation with electron beams of tens to hundreds of kGy,
[0238] (ii) Transmission of electron beam to the reaction object (polymer) and generation of secondary electrons,
[0239] (iii) Dehydrogenation reaction and generation of free radicals in polymer chains based on secondary electrons,
[0240] (iv) based on the removal of adjacent hydrogen from free radicals and the movement of active sites,
[0241] (v) Cross-linking reaction or formation of polyene based on the recombination of free radicals.
[0242] Here, regarding the free radicals generated in the crystalline part, they exist for a long time due to lack of movement, and impurities and the like cannot enter the crystal, so the probability of reaction / quenching is low. This kind of free radical species is called a stable free radical (Stable Radical), which remains for a long time of several months, and its life span is clearly determined by ESR measurement. As a result, it can be considered that there is a lack of cross-linking reaction in the crystal. However, the free radicals generated by the unbound molecular chains that exist slightly inside the crystal or the surrounding crystalline-amorphous intermediate layer have a slightly longer life span. This kind of free radical species is called a persistent free radical (Persistent Radical), and it can be considered that in a mobile environment, cross-linking reactions between molecular chains occur with a high probability. On the other hand, the mobility of the non-crystalline part is very high, so it can be considered that the free radical species generated have a short life span, and not only cross-linking reactions between molecular chains occur with a high probability, but also polyene reactions occur within a molecular chain with a high probability.
[0243] As described above, it can be inferred that, in the microscopic field at the crystal level, the cross-linking reaction based on EB cross-linking is locally present inside or around the crystal.
[0244] (III) Cross-linking reaction mechanism based on chemical reaction
[0245] As mentioned above, there are crystalline parts and amorphous parts in polyolefin resins. However, the aforementioned functional groups are not present inside the crystal due to steric hindrance, but are locally present in the amorphous part. It is well known that units such as methyl groups slightly contained in the polyethylene chain are sometimes introduced into the crystal, but grafts with a larger volume than ethyl groups are not introduced into the crystal ("Basic Polymer Chemistry", published by Tokyo Chemical Dojin). Therefore, the crosslinking points based on a reaction different from electron beam crosslinking are only locally present in the amorphous part.
[0246] (IV) Relationship between different cross-linking structures and effects
[0247] In order to form a cross-linked structure in the microporous membrane, it is preferred to use a combination of a functional group in a polyolefin resin and a chemical substance contained in a power storage device, or to use a chemical substance contained in a power storage device as a catalyst. In a cross-linking reaction based on a chemical reaction inside a power storage device, the form of the reaction product is different depending on the raw materials or catalyst used. In the research until the present invention was realized, in order to clarify the cross-linked structure and clarify the physical property changes of the microporous membrane accompanying the structural changes, the phenomenon was clarified by the following experiment.
[0248] For films that were not crosslinked by EB or chemically crosslinked (before) and chemically crosslinked films, the behavior of both during crystal melting was investigated by fuse / fuse characteristics test. As a result, the fuse temperature of the film that was crosslinked by EB became significantly higher, and the fusing temperature rose to more than 200°C. On the other hand, no change in the fuse temperature was observed for the chemically crosslinked film before and after the crosslinking treatment, and it can be confirmed that the fusing temperature rose to more than 200°C. Therefore, for the fuse characteristics caused by crystal melting, crosslinking occurred around the crystal part of the EB crosslinked film, so it can be considered that the reason is the increase in melting temperature and the decrease in melting speed. On the other hand, there is no crosslinking structure in the crystal part of the chemically crosslinked film, so it is judged that it does not change the fuse characteristics. In addition, in the high temperature region around 200°C, both have a crosslinking structure after the crystal melts, so the resin as a whole can be stabilized in a gel state, and good fusing characteristics can be obtained.
[0249] The above findings are summarized in Table 1 below.
[0250] [Table 1]
[0251] project Electron beam cross-linking Chemical reaction crosslinking Cross-linking site In the crystal, crystal-amorphous intermediate layer Amorphous part Film strength Increase No change Fuse function Deterioration or loss of function No change Anti-fuse function Improve in stages according to the radiation dose Reliably improve
[0252] In the first and third embodiments, (1) the condensation reaction of functional groups of polyolefins such as polyethylene and polypropylene may be, for example, a reaction via covalent bonds of two or more functional groups A contained in the polyolefin. In addition, (3) the reaction of functional groups of polyolefins with other types of functional groups may be, for example, a reaction via covalent bonds of functional groups A and functional groups B contained in the polyolefin.
[0253] In the first embodiment and the third embodiment, in (2) the reaction between the functional group of a polyolefin such as polyethylene or polypropylene and the chemical substance inside the power storage device, for example, the functional group A contained in the polyolefin can form a covalent bond or a coordination bond with any of the electrolyte, electrolyte solution, electrode active material, additive or their decomposition products contained in the power storage device. In addition, according to reaction (2), a cross-linked structure is formed not only inside the diaphragm, but also between the diaphragm and the electrode or between the diaphragm and the solid electrolyte interface (SEI), which can improve the strength between the multiple components of the power storage device.
[0254] From the viewpoint of forming a cross-linked structure of the amorphous part and achieving both shutdown function and high-temperature rupture resistance, the hybrid storage modulus ratio (R) defined by the following formula (I) of the microporous membranes according to the first embodiment, the second embodiment, the third embodiment, and the fourth embodiment is E’x ) and / or the mixed loss modulus ratio (R E”x ) is preferably 1.2 to 20 times, more preferably 2.0 to 18 times, and further preferably 3.0 to 16.5 times.
[0255] R E’X =E' Z / E' z0 (I)
[0256] {where E' Z The storage modulus is measured in a temperature range of 160° C. to 300° C. after a crosslinking reaction of the microporous membrane has been carried out in the power storage device, and
[0257] E' z0 The storage modulus is measured in the temperature range of 160°C to 300°C before the microporous membrane is assembled into the power storage device.
[0258] R E”X =E” Z / E” Z0 (III)
[0259] {where, E” Z The loss modulus is measured in a temperature range of 160° C. to 300° C. after a crosslinking reaction of the microporous membrane has been carried out in the power storage device, and
[0260] E” Z0 This is the loss modulus measured in the temperature range of 160°C to 300°C before the microporous membrane is assembled into the power storage device.
[0261] It should be noted that E' Z and E' z0 and E” Z and E” z0 It means: when 160°C to 300°C is set as the widest temperature range, the average value of the storage modulus or loss modulus measured within the set temperature range of the measuring device. In the case of a laminated film, only the polyolefin-based microporous film is removed from the laminated film and the storage modulus E' is measured. Z and E' z0 And loss modulus E" Z and E” z0 . E' Z , E' z0 , E” Z or E" z0 The measurement conditions of the elastic modulus are described in the examples.
[0262] From the viewpoint of forming a cross-linked structure of the amorphous part and achieving both shutdown function and high-temperature rupture resistance, the hybrid storage modulus ratio (R) defined by the following formula (II) of the separators according to the first embodiment, the second embodiment, the third embodiment, and the fourth embodiment is E’mix ) and / or the mixed loss modulus ratio (R E”mix ) is preferably 1.2 to 20 times, more preferably 2.0 to 18 times, and further preferably 3.0 to 17 times.
[0263] R E’mix =E' / E' 0 (II)
[0264] {wherein, E' is the storage modulus of the microporous membrane having a cross-linked structure in the amorphous part measured at 160°C to 300°C, and,
[0265] E' 0 It is the storage modulus of a microporous film without a crosslinked structure in the amorphous part measured at 160°C to 300°C.
[0266] R E”mix =E” / E” 0 (IV)
[0267] {wherein, E" is the loss modulus measured at 160°C to 300°C when the microporous membrane has a crosslinked structure in the amorphous portion, and,
[0268] E” 0This is the loss modulus of a microporous film without a crosslinked structure in the amorphous part measured at 160°C to 300°C.
[0269] It should be noted that E' and E' 0 and E” and E” 0 They refer to the average values of the storage modulus or loss modulus measured within the set temperature range of the measuring device when the widest temperature range is 160°C to 300°C. In the case of a laminated film, only the polyolefin-based microporous film is removed from the laminated film and the storage modulus E' and E' are measured. 0 and loss modulus E” and E” 0 . E', E' 0 , E” or E” 0 The measurement conditions of the elastic modulus are described in the examples.
[0270] The constituent elements of the microporous membranes described in the first embodiment, the second embodiment, the third embodiment, and the fourth embodiment will be described below.
[0271] 〔Polyolefin〕
[0272] As the polyolefin constituting the microporous membrane, there is no particular limitation, and examples thereof include homopolymers of ethylene or propylene, or copolymers formed by at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene and norbornene. Among them, from the viewpoint of easily realizing porousness in wet or dry type, it is preferably high-density polyethylene, low-density polyethylene, ultra-high molecular weight polyethylene (UHMWPE), polypropylene, polybutene or a combination thereof, more preferably polypropylene. In general, the weight average molecular weight of known UHMWPE is more than 1,000,000. It should be noted that the polyolefin can be used alone or in combination of two or more.
[0273] In addition, the weight average molecular weight (Mw) of the polyolefin can be arbitrarily determined in such a way that the dispersion degree (Mw / Mn) of the condition (B) described above is 15 or less, and is preferably 10,000 to 2,000,000, more preferably 20,000 to 1,500,000, and further preferably 30,000 to 1,000,000 from the viewpoint of the heat shrinkage of the microporous membrane and the safety of the power storage device. From the same viewpoint, the microporous membrane preferably contains 3 to 25% by mass, more preferably 5 to 20% by mass of a polyolefin having an Mw of 10,000 to 2,000,000 relative to the entire raw material polyolefin.
[0274] [Polyolefins having one or more functional groups]
[0275] From the viewpoint of forming a cross-linked structure, resistance to redox degradation and a dense and uniform porous structure, in the microporous membrane, as a polyolefin having one or more functional groups, it is preferred to include a functional group-modified polyolefin or a polyolefin having a monomer having a functional group copolymerized. It should be noted that in this specification, a functional group-modified polyolefin refers to a substance obtained by bonding a functional group after the manufacture of a polyolefin. The functional group can be bonded to a polyolefin skeleton or introduced into a comonomer, preferably participating in the selective crosslinking of a non-crystalline portion of a polyolefin, and can be, for example, selected from a carboxyl group, a hydroxyl group, a carbonyl group, a polymerizable unsaturated hydrocarbon group, an isocyanate group, an epoxy group, a silanol group, a hydrazide group, a carbodiimide group, an oxazoline group, an acetoacetyl group, an aziridine group, an ester group, an active ester group, a carbonate group, an azido group, a chain or cyclic hydrocarbon group containing heteroatoms, an amino group, a sulfhydryl group, a metal chelate group and a halogen-containing group. At least one of the group consisting of.
[0276] 〔Various polypropylenes〕
[0277] From the viewpoints of the strength, ion permeability, resistance to redox degradation, and dense and uniform porous structure of the microporous membrane, the microporous membrane preferably comprises both a polyolefin having one or more functional groups and another polyolefin, and more preferably comprises both a first polypropylene (A) and a second polypropylene (B) that can be distinguished from the polypropylene (A) and has a functional group.
[0278] From the viewpoint of the strength, film forming properties, productivity and pore opening of the microporous film, the first polypropylene (A) is preferably a homopolypropylene (A) satisfying the following conditions (P1) to (P3).
[0279] (P1) MFR when measured under the conditions of a temperature of 230°C and a mass of 2.16 kg is 2.5 g / 10 min or less;
[0280] (P2) the value obtained by dividing the weight average molecular weight Mw by the number average molecular weight Mn (Mw / Mn) is 10 or less; and
[0281] (P3) density is 0.89g / cm 3 above.
[0282] For the condition (P1) of the homopolypropylene (A), the MFR is more preferably 0.25 to 2.4 g / 10 min. For the condition (P2), the dispersion (Mw / Mn) of the homopolypropylene (A) is more preferably 4.9 to 9.0. For the condition (P3), the density of the homopolypropylene (A) is more preferably 0.90 g / cm 3 Above 0.96g / cm 3 Below, or 0.90g / cm 3 Above 0.93g / cm 3 the following.
[0283] On the other hand, the second polypropylene (B) having a functional group is a polypropylene having at least one functional group and not satisfying at least one of the above conditions (P1) to (P3), and may be a homopolymer or a copolymer. In the polypropylene (B), as a functional group, for example, at least one selected from the group consisting of a carboxyl group, a hydroxyl group, a carbonyl group, a polymerizable unsaturated hydrocarbon group, an isocyanate group, an epoxy group, a silanol group, a hydrazide group, a carbodiimide group, an oxazoline group, an acetoacetyl group, an aziridine group, an ester group, an active ester group, a carbonate group, an azido group, a chain or cyclic hydrocarbon group containing a hetero atom, an amino group, a sulfhydryl group, a metal chelate group, and a halogen-containing group may be present, and from the viewpoint of forming a crosslinked structure, silane-modified polypropylene is preferred.
[0284] When the polypropylene (A) and (B) are used together in the microporous membrane, the content of the polypropylene (B) in the microporous membrane is preferably 30% by mass or less, more preferably 4 to 25% by mass, and even more preferably 5 to 20% by mass, from the viewpoint of the balance between strength and crosslinking properties.
[0285] 〔Cross-linking reaction〕
[0286] The cross-linked structure of the microporous membrane helps to balance the shutdown function when used as a separator, the high temperature resistance to film breakage, and the safety of the storage device, and is preferably formed in the amorphous part of the polyolefin. The cross-linked structure can be formed by a reaction such as a covalent bond, a hydrogen bond, or a coordination bond. Among them, the reaction by a covalent bond is preferably at least one selected from the group consisting of the following reactions (I) to (IV).
[0287] (I) Condensation reaction of multiple identical functional groups
[0288] (II) Reaction between multiple different functional groups
[0289] (III) Chain condensation reaction between functional groups and electrolyte
[0290] (IV) Chain condensation reaction of the functional group with the additive.
[0291] Furthermore, the reaction via coordination bond is preferably the following reaction (V):
[0292] (V) A reaction in which a plurality of identical functional groups undergo cross-linking via coordination bonds with eluted metal ions.
[0293] Reaction (I)
[0294] The first functional group of the microporous membrane is represented by A, and a schematic route and specific examples of reaction (I) are shown below.
[0295] Schematic route of reaction (I)
[0296]
[0297] Examples of functional group A:
[0298] Silanol group, etc.
[0299] Specific example of reaction (I)
[0300]
[0301] {In the formula, R is an alkyl group or heteroalkyl group having 1 to 20 carbon atoms which may have a substituent.}
[0302] In the case where the functional group A used for reaction (I) is a silanol group, the polyolefin contained in the microporous membrane is preferably silane-grafted. The silane-grafted modified polyolefin is composed of a structure in which the main chain is a polyolefin and an alkoxysilyl group is grafted on the main chain. It should be noted that the alkoxides substituted with the above-mentioned alkoxysilyl groups can be listed as methoxide, ethoxide, butoxide, etc. For example, in the above formula, R can be methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, etc. In addition, the main chain and the graft are connected by a covalent bond, and structures such as alkyl, ether, glycol or ester can be listed. If the manufacturing process of the microporous membrane described in this embodiment is taken into account, the ratio of silicon to carbon (Si / C) of the silane-grafted modified polyolefin in the stage before the cross-linking treatment process is preferably 0.2 to 1.8%, more preferably 0.5 to 1.7%.
[0303] Reaction (II)
[0304] The first functional group of the microporous membrane is represented by A, and the second functional group is represented by B. The schematic route and specific examples of reaction (II) are shown below.
[0305] Schematic route of reaction (II)
[0306]
[0307] Examples of combinations of functional groups A and B:
[0308] Hydroxyl and carboxyl (esterification);
[0309] Carbonyl and alkyl (aldol condensation);
[0310] Halogen and carboxyl group (intramolecular condensation);
[0311] Alkoxy and alkyl (Claisen reaction);
[0312] Carbonyl group and anhydride group (Perkin reaction);
[0313] Amino and halogen;
[0314] Isocyanate and hydroxyl groups (urethane bond formation); and
[0315] (Oxazoline) and hydroxyl
[0316] Specific example 1 of reaction (II):
[0317]
[0318] Specific example 2 of reaction (II):
[0319] Reaction (I) and reaction (II) can be catalytically promoted, for example, by chemical substances inside the power storage device equipped with a microporous membrane as a separator. The chemical substances can be, for example, any of the electrolyte, electrolyte solution, electrode active material, additives or decomposition products thereof contained in the power storage device.
[0320] Reaction (III)
[0321] A first functional group of the microporous membrane is represented by A, and the electrolyte solution is represented by Sol. A schematic route and specific examples of reaction (III) are shown below.
[0322] Schematic route of reaction (III)
[0323]
[0324] Examples of functional group A:
[0325] Hydroxyl, carboxyl, amino, carbonyl, ether, isocyanate, etc.
[0326] Examples of electrolytes:
[0327] Electrolyte: LiPF 6 , LiBF 4 、LiN(SO 2 CF 3 ) 2 、LiSO 3 CF 3 , LiBC 4 O 8 (LiBOB) etc.
[0328] Non-aqueous solvent: ethylene carbonate, ethyl methyl carbonate or a mixture thereof
[0329] Specific example 1 of reaction (III):
[0330]
[0331] Specific example 2 of reaction (III):
[0332]
[0333] Reaction (IV)
[0334] The schematic scheme of reaction (IV) is shown below, where the first functional group of the microporous membrane is represented by A, the second functional group incorporated as desired is represented by B, and the additive is represented by Add.
[0335]
[0336] From the viewpoint of forming a covalent bond represented by a dotted line in the above route, reaction (IV) is preferably a nucleophilic substitution reaction, a nucleophilic addition reaction or a ring-opening reaction between the compound Rx constituting the microporous membrane and the compound Ry constituting the additive (Add). The compound Rx can be a polyolefin contained in the microporous membrane, such as polyethylene or polypropylene, and the polyolefin is preferably selected from the group consisting of -OH, -NH 2 The monomer is modified with at least one of the group consisting of -NH-, -COOH and -SH.
[0337] The plurality of compounds Rx are cross-linked via the compound Ry as an additive, and therefore the compound Ry preferably has two or more linking reaction units y 1 . Multiple linked reaction units 1 As long as it can undergo nucleophilic substitution reaction, nucleophilic addition reaction or ring-opening reaction with the functional group x of compound Rx, it can be any structure or group, can be substituted or unsubstituted, can contain heteroatoms or inorganic substances, and can be the same or different. In addition, when compound Ry has a chain structure, multiple linked reaction units y 1 Each independently may be a terminal group, or incorporated into the main chain, or may be a side chain or a pendant group.
[0338] When reaction (IV) is a nucleophilic substitution reaction, as an example, the functional group x of compound Rx is regarded as a nucleophilic group, and the linking reaction unit y of compound Ry is regarded as 1 The following description will be made regarding the leaving group, but in this embodiment, the functional group x and the linking reaction unit y 1 Depending on their nucleophilicity, they can all become leaving groups.
[0339] From the viewpoint of nucleophilic reagent, the functional group x of compound Rx is preferably an oxygen nucleophilic group, a nitrogen nucleophilic group, or a sulfur nucleophilic group. Examples of oxygen nucleophilic groups include hydroxyl groups, alkoxy groups, ether groups, and carboxyl groups, among which -OH and -COOH are preferred. Examples of nitrogen nucleophilic groups include ammonium groups, primary amino groups, and secondary amino groups, among which -NH2 As the sulfur-based nucleophilic group, for example, -SH, a thioether group, etc. can be mentioned, and -SH is preferred.
[0340] When reaction (IV) is a nucleophilic substitution reaction, from the viewpoint of the leaving group, the linking reaction unit y of the compound Ry is 1 , preferably CH 3 SO 2 -、CH 3 CH 2 SO 2 -Alkylsulfonyl; Arylsulfonyl (-ArSO 2 -);CF 3 SO 2 -、CCl 3 SO 2 -Halogenated alkylsulfonyl; CH 3 SO 3 - -、CH 3 CH 2 SO 3 - -Alkyl sulfonate group; aryl sulfonate group (ArSO 3 - -);CF 3 SO 3 - -、CCl 3 SO 3 - - etc.; and heterocyclic groups, which can be used alone or in various combinations. As heteroatoms contained in the heterocyclic ring, nitrogen atoms, oxygen atoms, sulfur atoms, etc. can be listed, among which nitrogen atoms are preferred from the viewpoint of detachability. As the detaching group containing nitrogen atoms in the heterocyclic ring, the following formula (y 1 -1)~(y 1 -6) is a monovalent group.
[0341]
[0342] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0343]
[0344] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0345]
[0346] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0347]
[0348] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0349]
[0350] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0351]
[0352] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0353] Formula(y 1 -1)~(y 1 -6), X is a hydrogen atom or a monovalent substituent. Examples of the monovalent substituent include an alkyl group, a halogenated alkyl group, an alkoxy group, and a halogen atom.
[0354] When reaction (IV) is a nucleophilic substitution reaction and compound Ry has a chain structure, compound Ry preferably has a linking reaction unit y. 1 Based on the above, there is also a compound selected from the following formula (y 2 -1)~(y 2 -6) as the chain unit y 2 .
[0355]
[0356] {wherein, m is an integer from 0 to 20, and n is an integer from 1 to 20.}
[0357]
[0358] {wherein n is an integer from 1 to 20.}
[0359]
[0360] {wherein n is an integer from 1 to 20.}
[0361]
[0362] {wherein n is an integer from 1 to 20.}
[0363]
[0364] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.}
[0365]
[0366] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.}
[0367] In addition, the compound Ry contains a plurality of chain units y 2 In the case of , they may be the same as or different from each other, and their arrangement may be block or random.
[0368] In the formula (y 2 -1), m is an integer of 0 to 20, and preferably 1 to 18 from the viewpoint of the crosslinking network. 2 -1)~(y 2 -6), n is an integer of 1 to 20, and is preferably 2 to 19 or 3 to 16 from the viewpoint of the crosslinking network. 2 -5)~(y 2 -6), X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and is preferably a methylene group, an ethylene group, an n-propylene group, an n-butylene group, an n-hexylene group, an n-heptylene group, an n-octylene group, an n-dodecylene group, an o-phenylene group, an m-phenylene group or a p-phenylene group from the viewpoint of the stability of the chain structure.
[0369] When reaction (IV) is a nucleophilic substitution reaction, the functional group x of compound Rx and the linking reaction unit y of compound Ry are connected. 1 and chain unit y 2 Preferred combinations are shown in Tables 2 to 4 below.
[0370] [Table 2]
[0371]
[0372] [Table 3]
[0373]
[0374] [Table 4]
[0375]
[0376] As a specific example 1 of the nucleophilic substitution reaction, the functional group x of the polyolefin is -NH 2 , the linking reaction unit y of the additive (compound Ry) 1 is a skeleton derived from succinimide, and the chain unit y 2 For-(OC 2 H 5 ) n -The reaction route.
[0377] Specific example 1:
[0378]
[0379] As a specific example 2 of the nucleophilic substitution reaction, the functional group x of the polyolefin is -SH and -NH 2 , the linking reaction unit y of the additive (compound Ry) 1 is a nitrogen-containing cyclic skeleton, and the chain unit y 2 The reaction route for o-phenylene.
[0380] Specific example 2:
[0381]
[0382] When reaction (IV) is a nucleophilic addition reaction, the functional group x of compound Rx and the linking reaction unit y of compound Ry 1 In the nucleophilic addition reaction, the functional group x of the compound Rx is preferably an oxygen nucleophilic group, a nitrogen nucleophilic group, or a sulfur nucleophilic group. Examples of oxygen nucleophilic groups include hydroxyl groups, alkoxy groups, ether groups, and carboxyl groups, among which -OH and -COOH are preferred. Examples of nitrogen nucleophilic groups include ammonium groups, primary amino groups, and secondary amino groups, among which -NH 2 As the sulfur-based nucleophilic group, for example, -SH, a thioether group, etc. can be mentioned, and -SH is preferred.
[0383] In the nucleophilic addition reaction, from the viewpoint of addition reactivity or availability of raw materials, the linking reaction unit y of the compound Ry is 1 Preferably, it is selected from the following formula (Ay 1 -1)~(Ay 1 -6) at least one of the group consisting of the groups shown below.
[0384]
[0385] {In the formula, R is a hydrogen atom or a monovalent organic group.}
[0386]
[0387] Formula (Ay 1 -4), R is a hydrogen atom or a monovalent organic group, preferably a hydrogen atom, C 1~20 The alkyl group, alicyclic group or aromatic group is more preferably a hydrogen atom, a methyl group, an ethyl group, a cyclohexyl group or a phenyl group.
[0388] When reaction (IV) is a nucleophilic addition reaction, the functional group x of compound Rx and the linking reaction unit y of compound Ry are connected. 1 The preferred combinations are shown in Tables 5 and 6 below.
[0389] [Table 5]
[0390]
[0391] [Table 6]
[0392]
[0393] As a specific example of the nucleophilic addition reaction, the functional group x of the microporous membrane is -OH, and the linking reaction unit y of the additive (compound Ry) is shown below. 1 The reaction route for -NCO.
[0394] Specific examples:
[0395]
[0396] When reaction (IV) is a ring-opening reaction, the functional group x of compound Rx and the linking reaction unit y of compound Ry 1 The ring-opening reaction can occur. From the viewpoint of easy acquisition of raw materials, it is preferred to link the reaction unit y 1 From the same viewpoint, it is more preferable to link the reaction unit y 1 It is an epoxy group, and more preferably the compound Ry has at least two epoxy groups, and is further preferably a diepoxide compound.
[0397] When reaction (IV) is a ring-opening reaction, the functional group x of compound Rx is preferably selected from -OH, -NH 2 , -NH-, -COOH and -SH, and / or the linking reaction unit y of the compound Ry 1 Preferably, the following formula (ROy 1 - at least two groups shown in 1).
[0398]
[0399] {In the formula, each of the multiple Xs is independently a hydrogen atom or a monovalent substituent.}
[0400] In the formula (ROy 1 -1), each of the plurality of X's is independently a hydrogen atom or a monovalent substituent, preferably a hydrogen atom, C 1~20 An alkyl group, an alicyclic group or an aromatic group, more preferably a hydrogen atom, a methyl group, an ethyl group, a cyclohexyl group or a phenyl group. For the epoxy ring-opening reaction, the functional group x of the compound Rx is linked to the linking reaction unit y of the compound Ry. 1 The preferred combinations are shown in Table 7 below.
[0401] [Table 7]
[0402]
[0403] Reaction (V)
[0404] The first functional group of the microporous membrane is represented by A, and the metal ion is represented by M n+ , a schematic route of reaction (V) and examples of functional group A are shown below.
[0405] Schematic route of reaction (V)
[0406]
[0407] Examples of functional group A: -CHO, -COOH, anhydride, -COO - wait
[0408] In the above route, the metal ion M n+ Preferably, the metal ions eluted from the power storage device (hereinafter also referred to as eluted metal ions) may be selected from the group consisting of Zn 2+ , Mn 2+ 、Co 3+ 、Ni 2+ and Li + The following example shows that the functional group A is -COO - The coordination bond at the time.
[0409]
[0410] The following shows that the functional group A is -COOH and the eluted metal ion is Zn 2+ The specific route of the reaction (V).
[0411]
[0412] In the above route, hydrofluoric acid (HF) may be derived from any of the electrolyte, electrolyte solution, electrode active material, additives, or decomposed products or hygroscopic products thereof contained in the power storage device, for example, according to the charge and discharge cycle of the power storage device.
[0413] (Other contents)
[0414] The microporous film may contain, in addition to the polyolefin, known additives such as a dehydration condensation catalyst, metal soaps such as calcium stearate or zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, and a coloring pigment, as desired.
[0415] [Characteristics of microporous membrane]
[0416] The following properties of the microporous membrane are described for a case where the microporous membrane for an electricity storage device is a flat membrane. However, when the microporous membrane for an electricity storage device is in the form of a laminated membrane, the properties can be measured after removing layers other than the microporous membrane from the laminated membrane.
[0417] The porosity of the microporous membrane is preferably 20% or more, more preferably 30% or more, and further preferably 39% or more or 42% or more. By making the porosity of the microporous membrane 20% or more, when used as a separator of a lithium ion storage device, there is a tendency to further improve the followability of the rapid movement of lithium ions. On the other hand, the porosity of the microporous membrane is preferably 90% or less, more preferably 80% or less, and further preferably 50% or less. By making the porosity of the microporous membrane 90% or less, there is a tendency to further improve the membrane strength and further suppress self-discharge.
[0418] The air permeability resistance of the microporous membrane is preferably more than 1 second, more preferably more than 50 seconds, more preferably more than 100 seconds, more preferably more than 150 seconds or more than 200 seconds relative to the volume of the membrane per 100ml. By making the air permeability resistance of the microporous membrane more than 1 second, there is a tendency to further improve the balance between the film thickness, porosity and average pore size. In addition, the air permeability resistance of the microporous membrane is preferably less than 450 seconds, more preferably less than 420 seconds. By making the air permeability resistance of the microporous membrane less than 450 seconds, there is a tendency to further improve ion permeability.
[0419] The tensile strength of the microporous film is related to the orientation ratio MD / TD of the condition (D) described above, and is preferably 900 to 3000 kg / cm 2 , more preferably 1000 to 2500 kg / cm 2 , more preferably 1210 to 2270 kg / cm 2 , preferably 100 to 1500 kg / cm2 in TD (direction perpendicular to MD, film width direction). 2 , more preferably 129 to 1310 kg / cm 2 .
[0420] The film thickness of the microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, and further preferably 3.0 μm or more, 4.0 μm or more, or 5.5 μm or more. By making the film thickness of the microporous membrane 1.0 μm or more, there is a tendency for the membrane strength to be further improved. In addition, the film thickness of the microporous membrane is preferably 500 μm or less, more preferably 100 μm or less, and further preferably 80 μm or less, 22 μm or less, or 19 μm or less. By making the film thickness of the microporous membrane 500 μm or less, there is a tendency for ion permeability to be further improved. When the microporous membrane is used as a separator for a lithium ion secondary battery, the film thickness of the microporous membrane is preferably 1.0 to 25 μm, more preferably 3.0 to 22 μm, and further preferably 13 to 18 μm.
[0421] From the viewpoint of achieving a balance between film rupture resistance and device safety, the puncture strength of the microporous membrane is preferably 200 to 500 gf, more preferably 218 to 481 gf or 227 to 450 gf.
[0422] [Method for producing microporous membrane]
[0423] The method for manufacturing a microporous membrane may include the following steps:
[0424] A process for forming a polyolefin resin composition;
[0425] A process for opening pores in a polyolefin resin composition; and
[0426] Heat treatment process of open-pore compounds.
[0427] The following description is made with respect to the case of a microporous membrane (flat membrane), but it does not mean that forms other than flat membranes are excluded.
[0428] The polyolefin resin composition can be produced by a melt-kneading method using a polyolefin resin and other materials using a single-screw or twin-screw extruder.
[0429] The materials to be kneaded in the kneading step can be determined according to the pore-forming step to be performed later. This is because the pore-forming step can be performed by a known dry method and / or wet method.
[0430] As dry methods, there are a method of forming pores by subjecting an unstretched sheet containing incompatible particles such as inorganic particles and polyolefin to stretching and withdrawal to cause separation of interfaces between different raw materials, a lamellar pore method, a β-crystal pore method, and the like.
[0431] The lamellar opening method is a method in which, when a sheet is formed by melt extrusion of a resin, an unstretched sheet having a crystalline lamellar structure is obtained by controlling the melt crystallization conditions, and the obtained unstretched sheet is stretched to crack the lamellar interface, thereby forming holes. In the lamellar opening method, for example, a circular die extrusion method can be used. In the circular die extrusion method, for example, a molten kneaded product of a polypropylene resin composition is blown from a ring-shaped die mainly along the MD to obtain a highly crystalline MD-oriented original roll.
[0432] The β-crystal opening method is a method in which an unstretched sheet having a β-crystal with a low crystal density is produced during melt extrusion of polypropylene (PP), and the produced unstretched sheet is stretched to convert its crystal form into an α-crystal with a high crystal density, and pores are formed by utilizing the difference in crystal density between the two. As a β-crystal nucleating agent, for example, 1:2,6-naphthalene dicarboxylic acid dicyclohexylamide can be used, and a β-crystal nucleating agent and an antioxidant are preferably used in combination. In the second and fourth embodiments, β-crystal active PP can be used, so the β-crystal opening method is preferred.
[0433] As a wet method, the following methods can be used: using a mixer, polyolefin, other desired resins and plasticizers or inorganic materials are kneaded to form a sheet, and after stretching as needed, the pore-forming material is extracted from the sheet; after the polyolefin resin composition is dissolved, it is immersed in a poor solvent for polyolefin to solidify the polyolefin, and the solvent is removed at the same time, etc.
[0434] As a plasticizer, there is no particular limitation, and examples thereof include organic compounds that can form a uniform solution with polyolefin at a temperature below the boiling point. More specifically, decalin, xylene, dioctyl phthalate, dibutyl phthalate, stearyl alcohol, oleyl alcohol, decanol, nonanol, diphenyl ether, n-decane, n-dodecane, paraffin oil, etc. can be listed. Among these, paraffin oil and dioctyl phthalate are preferred. One type of plasticizer can be used alone, or two or more types can be used in combination.
[0435] From the viewpoint of maintaining the crosslinking property of the microporous membrane until it is accommodated in the power storage device regardless of whether the dry method or the wet method is used, the method for producing the microporous membrane preferably does not include a step of contacting the latent crosslinkable polyolefin with a crosslinking agent, other reactive compounds, functional groups of other compounds, a crosslinking promoting catalyst, etc. In addition, the polyolefin resin composition may contain additives such as fluorine-based flow modifiers, waxes, crystal nucleating materials, antioxidants, metal soaps such as aliphatic carboxylic acid metal salts, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, coloring pigments, etc. as long as the crosslinking property of the microporous membrane is maintained.
[0436] In order to suppress the shrinkage of the microporous membrane, a heat treatment process of the open-pore material can be performed for the purpose of heat setting after the stretching process or after the pore forming. As heat treatment, there can be listed: a stretching operation performed in a specific temperature atmosphere and a specific stretching rate for the purpose of adjusting physical properties; and / or a relaxation operation performed in a specific temperature atmosphere and a specific relaxation rate for the purpose of reducing tensile stress. The relaxation operation can be performed after the stretching operation. These heat treatments can be performed using a tenter or a roller stretching machine.
[0437] [Electricity storage device]
[0438] The microporous membrane described in the first embodiment, the second embodiment, the third embodiment and the fourth embodiment can be used in an electrical storage device. Generally speaking, the electrical storage device comprises an outer packaging body, a positive electrode, a negative electrode, a separator disposed between the positive and negative electrodes, and an electrolyte. If the microporous membrane described in these embodiments is contained in the outer packaging body of the device, the functional group-modified polyolefin or the functional group-grafted copolymerized polyolefin formed in the manufacturing process of the microporous membrane reacts with the chemical substances contained in the electrolyte or the additive to form a cross-linked structure, and therefore, the manufactured electrical storage device has a cross-linked structure. From the viewpoint of maintaining the cross-linking property of the microporous membrane until it is contained in the electrical storage device and then improving the safety of the electrical storage device, the microporous membrane is preferably disposed between the positive and negative electrodes as a separator. If the microporous membrane is contained in the electrical storage device as a separator, a cross-linked structure is formed, so that it can adapt to the manufacturing process of the previous electrical storage device and can undergo a cross-linking reaction after the device is manufactured to improve the safety of the electrical storage device.
[0439] As the power storage device, specifically, lithium batteries, lithium secondary batteries, lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel-hydrogen batteries, nickel-cadmium batteries, double-layer capacitors, lithium ion capacitors, redox flow batteries, lithium-sulfur batteries, lithium-air batteries, zinc-air batteries, etc. can be listed. Among these, from the viewpoint of practicality, preferably lithium batteries, lithium secondary batteries, lithium ion secondary batteries, nickel-hydrogen batteries or lithium ion capacitors, more preferably lithium batteries or lithium ion secondary batteries.
[0440] 〔Lithium-ion secondary battery〕
[0441] Lithium-ion secondary batteries use lithium transition metal oxides such as lithium cobalt oxide and lithium cobalt composite oxide as the positive electrode, carbon materials such as graphite and black lead as the negative electrode, and LiPF 6A storage battery that uses an organic solvent of a lithium salt such as lithium salt as an electrolyte. During the charge / discharge of a lithium ion secondary battery, ionized lithium moves back and forth between the electrodes. In addition, since it is necessary to suppress the contact between the electrodes while allowing the aforementioned ionized lithium to move between the electrodes at a relatively high speed, a separator is configured between the electrodes.
[0442] Example
[0443] The present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples unless the gist of the present invention is exceeded. The raw materials used and the methods for evaluating various properties of the microporous membrane are as follows.
[0444] [Determination of melt flow rate (MFR)]
[0445] The melt flow rate (MFR) is expressed as a value measured for a polypropylene resin under conditions of 230° C. and 2.16 kg in accordance with JIS K 7210 (unit: g / 10 minutes).
[0446] [Measurement by GPC (Gel Permeation Chromatography)]
[0447] Using AGILENT PL-GPC220, standard polystyrene was measured under the following conditions to prepare a calibration curve. In addition, for each of the following polymers, chromatograms were measured under the same conditions, and based on the calibration curve, the weight average molecular weight Mw of each polymer was divided by the number average molecular weight Mn by the following method.
[0448] Column: TSKgel GMHHR-H(20)HT (7.8mm I.D.×30cm) 2 pieces
[0449] Mobile phase: 1,2,4-trichlorobenzene
[0450] Detector: RI
[0451] Column temperature: 160°C
[0452] Sample concentration: 1mg / ml
[0453] Calibration curve: polystyrene
[0454] [Measurement of wide-angle X-ray scattering]
[0455] Ultima-IV manufactured by Rigaku Corporation was used for the measurement. Cu-Kα rays were incident on the diaphragm as a sample, and the diffracted light was detected using D / tex Uitra. The measurement conditions were that the distance between the sample and the detector was 285 mm, the excitation voltage was 40 kV, and the current was 40 mA. The optical system used a concentrated optical system, and the slit conditions were DS = 1 / 2°, SS = open, and longitudinal slit = 10 mm. The value obtained by dividing the measured oriented crystal ratio in the MD direction by the oriented crystal ratio in the TD direction was calculated as the MD / TD orientation ratio.
[0456] [Thickness (μm)]
[0457] The thickness of the porous film was measured at room temperature 23±2°C using a digital indicator IDC112 manufactured by MITUTOYO CORPORATION.
[0458] [Porosity (%)]
[0459] A 5 cm×5 cm square sample was cut out from the porous film, and the porosity was calculated from the volume and mass of the sample using the following formula.
[0460] Porosity (%) = (volume (cm 3 )-mass (g) / density of resin composition (g / cm 3 )) / Volume(cm 3 )×100
[0461] [Breathability resistance (seconds / 100ml)]
[0462] The air permeability resistance of the microporous membrane was measured using a Gray-type air permeometer in accordance with JIS P-8117.
[0463] [Puncture Strength]
[0464] A hemispherical needle with a front end having a radius of 0.5 mm was prepared, and a microporous membrane was sandwiched between two plates having an opening with a diameter (dia.) of 11 mm, and a needle, a microporous membrane, and a plate were set. Using "MX2-50N" manufactured by IMADA, a puncture test was performed under the conditions of a curvature radius of 0.5 mm at the front end of the needle, an opening diameter of 11 mm in the microporous membrane holding plate, and a puncture speed of 25 mm / min, the needle was brought into contact with the microporous membrane, and the maximum puncture load (i.e., puncture strength (gf)) was measured.
[0465] [Determination of storage modulus, loss modulus and transition temperature]
[0466] The dynamic viscoelasticity of the diaphragm was measured using a dynamic viscoelasticity measuring device to calculate the storage modulus (E'), loss modulus (E"), and the transition temperature between the rubber flat region and the crystalline melt flow region. The storage modulus change ratio (RE’X ) is calculated according to the following formula (I), the mixed storage modulus ratio (R E’mix ) is calculated according to the following formula (II), the loss modulus ratio (R E”X ) is calculated according to the following formula (III), the mixed loss modulus ratio (R E”mix ) is calculated according to the following formula (IV). It should be noted that the measurement conditions are as shown in the following (i) to (iv).
[0467] (i) Dynamic viscoelasticity measurements were performed under the following conditions:
[0468] Atmosphere: Nitrogen
[0469] · Measurement device used: RSA-G2 (manufactured by TA Instruments)
[0470] Sample film thickness: 5 μm to 50 μm (all samples are measured on one sheet regardless of their film thickness)
[0471] ·Measurement temperature range: -50~300℃
[0472] Heating rate: 10℃ / min
[0473] ·Measurement frequency: 1Hz
[0474] Deformation mode: Sine wave stretching mode (Linear tension)
[0475] Initial value of static tensile load: 0.5N
[0476] Initial (at 25°C) gap distance: 25mm
[0477] Automatic strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N).
[0478] (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each cycle motion, and the sinusoidal load refers to the oscillating stress centered on the static tensile load.
[0479] (iii) Sine wave tensile mode refers to measuring vibration stress while performing periodic motion at a fixed amplitude of 0.2%. At this time, the gap distance and static tensile load are changed in such a way that the difference between the static tensile load and the sine wave load is within 20%, and the vibration stress is measured. When the sine wave load is less than 0.02N, the amplitude value is amplified in such a way that the sine wave load is within 5N and the increase in the amplitude value is within 25%, and the vibration stress is measured.
[0480] (iv) The storage modulus and loss modulus are calculated from the obtained relationship between the sinusoidal wave load and the amplitude value and the following equation.
[0481] ζ * =ζ 0 Exp[i(ωt+δ)],
[0482] ε * =ε 0 Exp(iωt),
[0483] ζ * =E * ·ε *
[0484] E * =E'+iE"
[0485] {where, ζ * :Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : complex modulus, E': storage modulus, E': loss modulus
[0486] Vibration stress: Sinusoidal load / initial cross-sectional area
[0487] Static tensile load: The load at the minimum point of vibration stress in each cycle (the minimum point of gap distance in each cycle)
[0488] Sine wave load: The difference between the measured vibration stress and the static tensile load.
[0489] E' Z and E' Z0 and E” Z and E” Z0 The maximum value of each storage modulus or each loss modulus at 160°C to 300°C in the dynamic viscoelasticity measurement data is set. E' and E' 0 and E” and E” 0 The average value of each storage modulus or each loss modulus at 160° C. to 300° C. in the dynamic viscoelasticity measurement data was set.
[0490] R E’X =E' Z / E' Z0 (I) Comparison before and after adding to the sample pool
[0491] R E’mix =E' / E' 0 (II) Comparison of the presence and absence of cross-linked structure in the amorphous part
[0492] R E”X =E” Z / E” Z0(III) Comparison before and after adding to the sample pool
[0493] R E”mix =E” / E” 0 (IV) Comparison of the presence and absence of cross-linked structure in the amorphous part
[0494] An example of a graph for explaining the relationship between temperature and storage modulus is shown in Figure 3 .like Figure 3 As shown in FIG. 1 , the storage modulus of the reference film (a separator for a power storage device without a crosslinked amorphous portion structure) in the temperature range of -50°C to 310°C is compared with that of the crosslinked film. Figure 3 The transition temperature between the rubber flat region and the crystal melting flow region can be confirmed. It should be noted that the transition temperature is the temperature at the intersection of a straight line extending the high temperature side baseline toward the low temperature side and a tangent line drawn at the inflection point of the curve of the crystal melting change portion.
[0495] An example of a graph for explaining the relationship between temperature and loss modulus is shown in Figure 4 . Figure 4 The loss modulus of the reference film (a separator for a storage device not containing silane-grafted modified polyolefin) and the cross-linked film in the temperature range of -50°C to 310°C are compared, and the loss modulus of the cross-linked film is compared with that of the reference film (a separator for a storage device not containing silane-grafted modified polyolefin). Figure 3 In the art, storage modulus and loss modulus can be interchanged according to the following formula.
[0496] tanδ=E” / E'
[0497] {wherein, tanδ represents the loss tangent, E' represents the storage modulus, and E" represents the loss modulus.}
[0498] It should be noted that in the mixed storage modulus ratio (R E’mix ) or mixed loss modulus ratio (R E”mix ) was measured, as a separator for a power storage device having no amorphous crosslinked structure, a silane non-modified polyolefin-based microporous membrane having a gel degree of about 0% was used. 0、 E" and E" 0 When no fracture of the sample (sharp decrease in elastic modulus) was observed at 160°C to 300°C, the average value of the temperature at 160°C to 300°C was used for calculation. When fracture of the sample was observed at 160°C to 300°C, the average value of the temperature from 160°C to the fracture point was used for calculation.
[0499] In this specification, the separator for a storage device without a crosslinked structure of an amorphous part may be a separator made of any one selected from the group consisting of polyethylene: X (viscosity average molecular weight of 100,000 to 400,000), ultra-high molecular weight PE: Y (viscosity average molecular weight of 400,000 to 800,000) and ultra-high molecular weight PE: Z (viscosity average molecular weight of 800,000 to 9,000,000) or two or three selected from the group consisting of X, Y and Z, and mixed in an arbitrary ratio. It should be noted that a polyolefin consisting of only a hydrocarbon skeleton of low-density polyethylene: LDPE, linear low-density polyethylene: LLDPE, polypropylene: PP, olefin-based thermoplastic elastomer, etc. may also be added to the mixed composition. More specifically, the separator for a storage device without a crosslinked structure of an amorphous part may refer to a polyolefin-based microporous membrane having a solid content change rate (hereinafter referred to as "gel degree") of 10% or less before and after heating at 160° C. in a decalin solution. It should be noted that when measuring the gel degree, the solid content refers only to the resin and does not include other materials such as inorganic substances.
[0500] On the other hand, the gel degree of the polyolefin-based microporous membrane having an amorphous portion crosslinked structure such as a silane crosslinked structure is preferably 30% or more, more preferably 70% or more.
[0501] [Tensile test]
[0502] The tensile strength in the MD and TD directions was measured using Instron Model 4201 according to the procedure of ASTM-882 and was determined as the breaking strength.
[0503] [Fuse / Melting (F / MD) Characteristics]
[0504] a. Preparation of positive electrode
[0505] Lithium cobalt composite oxide LiCoO as the positive electrode active material 2 92.2 mass%, 2.3 mass% of flaky graphite and acetylene black as conductive materials, and 3.2 mass% of polyvinylidene fluoride (PVDF) as a binder are dispersed in N-methylpyrrolidone (NMP) to prepare a slurry. The slurry is applied to one side of a 20 μm thick aluminum foil, which is the positive electrode collector, using a die coater, and dried at 130°C for 3 minutes, and then compression molded using a roller press. At this time, the coating amount of the positive electrode active material is 250 g / m 2 , the volume density of active material is 3.00g / cm 3 method to make adjustments.
[0506] b. Preparation of negative electrode
[0507] 96.9% by mass of artificial graphite as the negative electrode active material, 1.4% by mass of ammonium salt of carboxymethyl cellulose as a binder, and 1.7% by mass of styrene-butadiene copolymer latex were dispersed in purified water to prepare a slurry. The slurry was applied to one side of a copper foil with a thickness of 12 μm, which served as the negative electrode current collector, using a die coater, and after drying at 120°C for 3 minutes, compression molding was performed using a roller press. At this time, the amount of the negative electrode active material applied was 106 g / m 2 , the volume density of active material is 1.35g / cm 3 method to make adjustments.
[0508] c. Preparation of non-aqueous electrolyte
[0509] Using LiPF as solute 6 Prepared by dissolving in a mixed solvent of ethylene carbonate: ethyl methyl carbonate = 1:2 (volume ratio) in a concentration of 1.0 mol / L. The positive electrode, diaphragm and negative electrode, to which the resistance measurement wire is bonded with a conductive silver paste on the back of the aluminum foil, are cut into a circular shape with a diameter of 200 mm and overlapped, and c. an electrolyte containing an electrolyte is added to the obtained laminate, and the entire body is dyed. The aforementioned laminate is clamped in the center with a circular aluminum heater with a diameter of 600 mm, and the aluminum heater is pressurized from top to bottom to 0.5 MPa using a hydraulic jack to complete the preparation for the measurement. While heating the aforementioned laminate with an aluminum heater at a heating rate of 2°C / min, the resistance (Ω) between the electrodes is measured. The resistance between the electrodes rises together with the fuse of the diaphragm, and the temperature when the resistance exceeds 1000Ω for the first time is taken as the fuse temperature (shutdown temperature). In addition, the heating is further continued, and the temperature when the resistance drops below 1000Ω is taken as the melting temperature (film rupture temperature).
[0510] [Example 1]
[0511] <Method for preparing silane-grafted modified polyolefin>
[0512] The viscosity average molecular weight (Mv) of the raw material polyolefin used for silane grafting modified polyolefin can be 100,000 to 1,000,000, the weight average molecular weight (Mw) can be 30,000 to 920,000, and the number average molecular weight can be 10,000 to 150,000, and it can be propylene or butene copolymerized alpha olefin. While the raw material polyolefin is melt-kneaded by an extruder, an organic peroxide (di-tert-butyl peroxide) is added to generate free radicals in the alpha olefin polymer chain, and then a liquid of trimethoxyalkoxide-substituted vinyl silane is injected to introduce alkoxysilyl groups into the alpha olefin polymer by addition reaction to form a silane grafted structure. In addition, in order to simultaneously adjust the free radical concentration in the system, an appropriate amount of antioxidant (pentaerythritol tetrakis[3-(3,5-di-tetrabutyl-4-hydroxyphenyl) propionate]) is added to inhibit the chain reaction (gelation) in the alpha olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, pelletized, and then dried by heating at 80° C. for 2 days to remove moisture and unreacted trimethoxyalkoxide-substituted vinyl silane. The residual concentration of unreacted trimethoxyalkoxide-substituted vinyl silane in the pellets was about 1000 to 1500 ppm.
[0513] The silane-graft-modified polyolefin obtained by the above-mentioned production method is referred to as "silane-modified polypropylene" in the following Examples and Table 1.
[0514] <Production of Microporous Membrane (Single Layer)>
[0515] After dry blending a high molecular weight polypropylene resin (PP, MFR=0.25) with the above-mentioned silane-modified polypropylene at a mass ratio of PP: silane-modified polypropylene=95:5 (mass %), the mixture was melted using a 2.5-inch extruder and supplied to a ring-shaped mold using a gear pump. The temperature of the mold was set to 230°C, and the molten polymer was cooled by blowing air and then wound into a roll. The extruded precursor (original roll film) had a thickness of 15 μm, and then the original roll film was annealed at 130°C for 15 minutes. Then, the annealed film was cold stretched to 21% at room temperature, then hot stretched to 158% at 123°C, and relaxed to 128% at 126°C, thereby forming microporous and obtaining a microporous membrane. After the above-mentioned stretching and opening, the physical properties of the microporous membrane were measured. The results are shown in Table 8.
[0516] [Examples 2 to 6, Examples 8 to 10, Comparative Examples 1, 2, and 4]
[0517] A microporous membrane was obtained in the same manner as in Example 1 except that the raw materials were changed as shown in Table 8, and the obtained microporous membrane was evaluated.
[0518] [Example 7]
[0519] 0.2 mass % of 1:2,6-naphthalenedicarboxylic acid dicyclohexylamide as a β-crystal nucleating agent and 0.1 mass % of an antioxidant were mixed with polypropylene having an MFR of 2.4, and the mixture was put into a co-rotating twin-screw extruder and melt-kneaded at a set temperature of 270° C. The obtained strands were cooled and solidified in a water tank and cut in a pelletizer to produce pellets.
[0520] The obtained β-crystal active polypropylene pellets were dry-mixed with the above-mentioned silane-modified polypropylene at a mass ratio of β-crystal active polypropylene: silane-modified polypropylene = 95:5 (mass %), melted with a 2.5-inch extruder, and supplied to a ring-shaped mold using a gear pump. The temperature of the mold was set to 230°C, and the molten polymer was cooled by blowing air and then wound into a roll. The extruded precursor (original roll film) had a thickness of 15μm, and then the original roll film was annealed at 130°C for 15 minutes. Then, the annealed film was cold stretched to 21% at room temperature, then hot stretched to 158% at 123°C, and relaxed to 128% at 126°C, thereby forming microporous to obtain a microporous film. After the above-mentioned stretching and opening, the physical properties of the microporous film were measured. The results are shown in Table 8.
[0521] [Comparative Example 3]
[0522] A microporous membrane was obtained in the same manner as in Example 7 except that the raw materials were changed as shown in Table 8, and the obtained microporous membrane was evaluated.
[0523] [Table 8]
[0524]
Claims
1. A microporous membrane for an electrical storage device, comprising polypropylene, the polypropylene being β-crystal active, and having an amorphous portion crosslinked structure formed by crosslinking an amorphous portion of the polypropylene, The microporous membrane for a power storage device includes a homopolypropylene A satisfying the following conditions (P1) to (P3), and a polypropylene B having a functional group and not satisfying at least one of the conditions (P1) to (P3) as the polypropylene: (P1) MFR when measured under the conditions of a temperature of 230°C and a mass of 2.16 kg is 2.5 g / 10 min or less; (P2) the value Mw / Mn obtained by dividing the weight average molecular weight Mw by the number average molecular weight Mn is 10 or less; and (P3) density is 0.89g / cm 3 above.
2. The microporous membrane for an electrical storage device according to claim 1, wherein The amorphous portion cross-linked structure is formed by a reaction via any of covalent bonds, hydrogen bonds, or coordination bonds. The reaction via the covalent bond is at least one selected from the group consisting of the following reactions (I) to (IV): (I) condensation reaction of multiple identical functional groups; (II) reactions between multiple different functional groups; (III) chain condensation reaction between functional groups and electrolyte; (IV) chain condensation reaction between functional groups and additives, The reaction via the coordination bond is the following reaction (V): (V) A reaction in which a plurality of identical functional groups undergo cross-linking via coordination bonds with eluted metal ions.
3. The microporous membrane for an electrical storage device according to claim 1, wherein The amorphous portion is selectively cross-linked.
4. The microporous membrane for an electrical storage device according to claim 2, wherein The amorphous portion is selectively cross-linked.
5. The microporous membrane for an electrical storage device according to any one of claims 1 to 4, wherein The mixed storage modulus ratio R of the microporous membrane for a power storage device defined by the following formula (II) is: E’mix 1.2 to 20 times: R E’mix E' / E'0(II) In formula (II), E' is the storage modulus measured at 160°C to 300°C when the microporous membrane for a power storage device has the amorphous part crosslinked structure, and E'0 is the storage modulus of the microporous membrane for a power storage device having no amorphous crosslinked structure measured at 160°C to 300°C, and the storage modulus measurement conditions of E' or E'0 are defined by the following compositions (i) to (iv), (i) Dynamic viscoelasticity measurements were performed under the following conditions: Atmosphere: Nitrogen ·Measurement device used: RSA-G2 manufactured by TA Instruments Sample film thickness: 5 μm to 50 μm. Regardless of the sample film thickness, one sheet is used for measurement. ·Measurement temperature range: -50~300℃ Heating rate: 10℃ / min ·Measurement frequency: 1Hz Deformation mode: Sine wave stretching mode Initial value of static tensile load: 0.5N Initial gap distance at 25°C: 25mm Automatic strain adjustment: Enabled, where the range is 0.05-25% amplitude and 0.02-5N sine wave load; (ii) static tensile load refers to the midpoint between the maximum stress and the minimum stress in each cycle of motion, and sinusoidal load refers to the oscillating stress centered on the static tensile load; (iii) Sine wave tensile mode refers to measuring the vibration stress while performing periodic motion with a fixed amplitude of 0.2%. At this time, the gap distance and the static tensile load are changed in such a way that the difference between the static tensile load and the sine wave load is within 20% and the vibration stress is measured. In particular, when the sine wave load becomes less than 0.02N, the amplitude value is amplified in such a way that the sine wave load is within 5N and the increase in the amplitude value is within 25% and the vibration stress is measured; (iv) The storage modulus is calculated from the relationship between the obtained sinusoidal wave load and the amplitude value and the following formula: s * =σ0·Exp[i(ωt+δ)], e * =ε0·Exp(iωt)、 s * =E * ·e * E * =E'+iE” In the formula, σ * :Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : complex modulus, E': storage modulus, E': loss modulus Vibration stress: Sinusoidal load / initial cross-sectional area Static tensile load: The load at the minimum point of the vibration stress in each cycle, that is, the minimum point of the gap distance in each cycle. Sine Wave Load: The difference between the measured vibration stress and the static tensile load.
6. The microporous membrane for an electrical storage device according to any one of claims 1 to 4, wherein The content ratio of the polypropylene B is 4 mass % or more and 30 mass % or less.
7. The microporous membrane for an electrical storage device according to any one of claims 1 to 4, wherein The polypropylene B is silane-modified polypropylene.
8. The microporous membrane for an electrical storage device according to any one of claims 1 to 4, wherein The homopolypropylene A has an MFR of 0.25 g / 10 min or more, an Mw / Mn of 4.9 or more, and a density of 0.96 g / cm 3 the following.
Citation Information
Patent Citations
Porous film, and separator for cell and cell using the same
JP1997216964A
Porous membrane, battery separator comprising porous membrane, and manufacture thereof
JP1999144700A
Porous film, battery separator comprising porous film, and its production
JP1999172036A
Production of microporous resin film
JP2000319441A
Porous film
JP2001176484A